CoTRP/Graphene oxide composite as efficient electrode material for dissolved oxygen sensors. (20th December 2016) - Saravia, Lucas P.H.; Sukeri, Anandhakumar; Gonçalves, Josue M.; Aguirre-Araque, Juan S.; Brandão, Bruno B.N.S.; Matias, Tiago A.; Nakamura, Marcelo; Araki, Koiti; Toma, Henrique E.; Bertotti, Mauro
Graphical abstract: A novel CoTRP/Graphene oxide composite modified electrode was fabricated for oxygen reduction reaction via a direct four electron reduction pathway at very low overpotetnial (0.05 V) in aqueous solution. Highlights: Graphene oxide (GO) was modified with a Co porphyrin (CoTRP) film. Highly efficient and stable electrocatalyst for ORR in aqueous solution. The results of electrochemical measurements indicated that oxygen was reduced to H2 O via 4-electron transfer. The CoTRP/4GO modified electrode was used as probe for dissolved oxygen (DO) sensing. The CoTRP/4GO modified electrode exhibited higher electrocatalytic activity for DO reduction with good stability. Abstract: The preparation of the trifluoromethanesulfonate salt of [tetrakis-bisdimethylbipyridine chlororuthenium(II)]-5, 10, 15, 20-tetrapyridylporphyrinate cobalt(II) complex (CoTRP) and its composites with graphene oxide (GO) is described. The CoTRP molecules were found to lie flat on the GO surface, generating nanostructures that are more or less dispersible in aqueous media, depending on the relative amounts of CoTRP and GO. This feature can be used to tune the electrocatalytic activity of the composites in the oxygen reduction reaction (ORR) in neutral media. The material was characterized by transmission electron microscopy, Raman, UV–vis spectroscopy, atomic force microscopy and FT-IR and the results confirmed that CoTRP is strongly supported on GO through electrostatic interactions. The ORR activity of CoTRP/GO was evaluated by electrochemical techniques and a low overpotential (0.05 V) was noticed in the four-electron reduction of dioxygen. This value is dramatically shifted to positive potentials, by 0.88 V in relation to the glassy carbon electrode, and the electrode performance allows its use as effective sensor probe for continuous monitoring of dissolved oxygen (DO). Additionally, analytical parameters such as sensitivity, selectivity, reproducibility, lower detection limit (LOD) and stability were evaluated in order to demonstrate the suitability of the proposed sensor for continuous monitoring of dissolved oxygen.